БЎЛАЖАК ФИЗИКА ЎҚИТУВЧИЛАРИНИНГ КАСБИЙ КОМПЕТЕНТЛИГИНИ ТАКОМИЛЛАШТИРИШ - Мадаминов, Б.Н. (FAN va JAMIYAT, 2018)
The article contains the scientific data about some problems of developing professional competence of future teachers in Physics at higher educational establishments and the author tries to give the solution to these problems.